Light Deficiency Inhibits Growth by Affecting Photosynthesis Efficiency as well as JA and Ethylene Signaling in Endangered Plant Magnolia sinostellata - Danying Lu (MDPI AG, 2021)
The endangered plant Magnolia sinostellata largely grows in the understory of forest and suffers light deficiency stress. It is generally recognized that the interaction between plant development and growth environment is intricate; however, the underlying molecular regulatory pathways by which light deficiency induced growth inhibition remain obscure. To understand the physiological and molecular mechanisms of plant response to shading caused light deficiency, we performed photosynthesis efficiency analysis and comparative transcriptome analysis in M. sinostellata leaves, which were subjected to shading treatments of different durations. Most of the parameters relevant to the photosynthesis systems were altered as the result of light deficiency treatment, which was also confirmed by the transcriptome analysis. Gene Ontology and KEGG pathway enrichment analyses illustrated that most of differential expression genes (DEGs) were enriched in photosynthesis-related pathways. Light deficiency may have accelerated leaf abscission by impacting the photosynthesis efficiency and hormone signaling. Further, shading could repress the expression of stress responsive transcription factors and R-genes, which confer disease resistance. This study provides valuable insight into light deficiency-induced molecular regulatory pathways in M. sinostellata and offers a theoretical basis for conservation and cultivation improvements of Magnolia and other endangered woody plants.